2009
DOI: 10.1093/pcp/pcp170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Tri-Iron(III), Tri-Citrate Complex in the Xylem Sap of Iron-Deficient Tomato Resupplied with Iron: New Insights into Plant Iron Long-Distance Transport

Abstract: The identification of Fe transport forms in plant xylem sap is crucial to the understanding of long-distance Fe transport processes in plants. Previous studies have proposed that Fe may be transported as an Fe-citrate complex in plant xylem sap, but such a complex has never been detected. In this study we report the first direct and unequivocal identification of a natural Fe complex in plant xylem sap. A tri-Fe(III), tri-citrate complex (Fe(3)Cit(3)) was found in the xylem sap of Fe-deficient tomato (Solanum l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(162 citation statements)
references
References 54 publications
5
150
1
5
Order By: Relevance
“…23 More interestingly, a tri-Fe(III) tricitrate complex involved in Fe transport has been recently identified in xylem sap of tomato plants 24 and our results show that Fe(III)…”
Section: Al and Fe Are Complexed By Tricitratesupporting
confidence: 64%
See 1 more Smart Citation
“…23 More interestingly, a tri-Fe(III) tricitrate complex involved in Fe transport has been recently identified in xylem sap of tomato plants 24 and our results show that Fe(III)…”
Section: Al and Fe Are Complexed By Tricitratesupporting
confidence: 64%
“…The Fe complex was modelled as having an oxobridged tri-Fe(III) (Fe 3 Ocit 3 ) core and owing to its compact molecular geometry it is expected to permeate the plasmodesmata directly. 24 The authors also reported that while both Fe 3 cit 3 and Fe 3 Ocit 3 complexes could be identified in Fe-citrate standard solutions, only Fe 3 Ocit 3 was found in xylem samples. However, the Fe 3 cit 3 complex was detected in P. almogravensis root samples and represents the first report of this complex in biological samples (Fig.…”
Section: Al and Fe Are Complexed By Tricitratementioning
confidence: 95%
“…We describe an organic-acid-mediated mechanism that starts in the root tip and adjusts the root developmental response to low Pi. Organic acids have also been implicated in Fe uptake (30) and protection of the root from the entrance of toxic Al +3 ions (22,23). Taken all together, the evidence suggests that organic-acid exudation is a critical checkpoint in plant nutrition as these molecules do not only protect the root from the entry of toxic ions and enhance nutrient uptake, but also contribute to the modifications of root development that increase the soilexploration ability of the plant to enhance nutrient uptake.…”
Section: Malate Treatment Rescued the Expression Of Local-response Genesmentioning
confidence: 99%
“…Accumulation of Fe in the apoplast of cells in the RAM is required to activate the primary root response to low Pi availability (20). As carboxylateiron complexes have been reported to participate in iron transport and acquisition in plants ( [28][29][30] and malate efflux is affected in stop1 and almt1 mutants (21,22), we explored whether malate exudation plays a role in the Fe accumulation mechanism that is required to trigger primary root growth inhibition in response to low Pi availability. First, we tested whether malate is required for the accumulation of Fe in the apoplast of RAM cells using Perlsdiaminobenzidine (DAB) histochemical Fe staining, which allows the detection of changes in labile Fe +3 (20), on the root tips of WT, stop1, and almt1 in low-Pi media with or without 1 mM malate ( Fig.…”
Section: Almt1 Is Expressed In the Ram Of Arabidopsis Under Pi-deficimentioning
confidence: 99%
“…Citrate concentration is indeed markedly increased by iron starvation in xylem exudates (Brown, 1966;Ló pez-Millá n et al, 2000), and the acidic pH of this apoplastic fluid is compatible with the stability of the Fe-citrate complex. Only recently, however, has the presence of Fe-citrate complexes, in the form of tri-Fe(III) tri-citrate and di-Fe(III) dicitrate, been detected in xylem exudates of tomato plants (Rellá n-Alvarez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%